1985
DOI: 10.1128/jcm.21.1.1-3.1985
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial pneumonia caused by a glucose-metabolizing strain of Neisseria cinerea

Abstract: We describe what appears to be the first reported case of nosocomial pneumonia caused by Neisseria cinerea. The isolate metabolized glucose when tested in BACTEC Neisseria Differentiation Kits (Johnston Laboratories), but did not produce detectable acid in cystine-Trypticase (BBL Microbiology Systems) agar medium or in modified oxidation-fermentation medium. Clinical laboratories that rely on the BACTEC method for differentiation of pathogenic neisseriae should be aware of the fact that N. cinerea may mimic N.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…In the past few years, reports of various rapid tests for the culture confirmation of Neisseria gonorrhoeae have appeared. However, decreased specificity (1)(2)(3)6), mainly due to cross-reactions with Neisseria cinerea, has been a problem with many of the tests. In an earlier study (4), we reported the sensitivity and specificity of the original Phadebact Gonococcus Test to be 94.3 and 100%, respectively.…”
mentioning
confidence: 99%
“…In the past few years, reports of various rapid tests for the culture confirmation of Neisseria gonorrhoeae have appeared. However, decreased specificity (1)(2)(3)6), mainly due to cross-reactions with Neisseria cinerea, has been a problem with many of the tests. In an earlier study (4), we reported the sensitivity and specificity of the original Phadebact Gonococcus Test to be 94.3 and 100%, respectively.…”
mentioning
confidence: 99%
“…or Moraxella sp.) are potential respiratory nosocomial pathogens in the human respiratory tract (Boyce et al 1985). Oxidase-negative Gram-negative cocci (as cultured from 'system 3') are generally not recognized pathogens, except Acinetobacter sp.…”
Section: Bacterial Survival In Anaesthesia Breathing Systemsmentioning
confidence: 99%
“…Some strains of N. gonorrhoeae, including those that belong to the AHU auxotype, are weak producers of acid from glucose and appear to be glucose negative (72). In contrast, some strains of N. cinerea traditionally considered to be glucose negative (58,95) have given positive glucose reactions in some rapid tests (18,34,63). Studies have shown that strains of N. cinerea do produce carbon dioxide from glucose (17).…”
Section: Rapid Tests For Identification Of Neisseria Andmentioning
confidence: 99%
“…However, problems have occurred with most rapid diagnostic tests which may result in the misidentification of nonpathogenic Neisseria spp. as Neisseria gonorrhoeae (18,26,30,34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation